Earnings Quality and Economic Narratives: Insights into Corporate Truth-Making from CFOs and Financial Standard Setters - Warsina, W.; Suswadi, S.; Budiana Kurniawati, Susilaningtyas; Dwanita Widodo, Zandra (Manunggal Halim Jaya, 2024)
This study investigates the perceptions of Chief Financial Officers (CFOs) in Indonesian companies regarding earnings quality and the factors influencing their reporting decisions. It aims to explore the implications of these perceptions for stakeholders, including investors and standard setters. Employing qualitative methodologies, the research collects data through in-depth interviews and surveys administered to CFOs across various sectors in Indonesia. The study examines the relationship between earnings quality and institutional ownership, credit ratings, and the professional backgrounds of CFOs. The findings reveal that nearly 95% of CFOs perceive earnings as critical for investors in valuing companies, with a strong emphasis on sustainability and the absence of one-time items as key attributes of high-quality earnings. Additionally, a significant correlation exists between institutional ownership and earnings quality, while CFOs with public accounting backgrounds report higher perceptions of earnings quality compared to their counterparts. The study highlights that firms with higher credit ratings tend to demonstrate greater earnings quality. The results underscore the importance of transparent and reliable financial reporting practices for CFOs, suggesting a need for improved accounting standards that address the complexities of earnings quality. Investors are encouraged to consider the sustainability of earnings when making investment decisions. This research contributes to the understanding of earnings quality in emerging markets, specifically within the context of Indonesian corporate governance. It bridges the gap between academic theories and practical insights from financial executives, offering valuable implications for future research and policy development.